UPAYA MEREKONSTRUKSI ULANG PENDIDIKAN NASIONAL - Ali Nupiah (Ta'dib, 2012)
Low quality of human resources in Indonesia can be separated from crucial problems that have not been solved until today. In general, those problems deal quality, distribution, relevance, efficiency and effectiveness of education. High rate of unemployment is indicates low relevance of education and the society’s demand. Consequently, curriculum development should provide the pupils with the ability to reach expected standard of life. Therefore, curriculum should be able to reflect real life which constantly develops and prepares the pupils to face and take part in any changes. Dealing with the demand, pupils should be provided with basic life skills and instrument skills. Those skills will be elaborated into competency in curriculum development and becomes the goals to be achieved in learning process and evaluation.Kata kunci: merekonsruksi ulang, pendidikan, nasional